THE OF GUIDED IMAGERY RELAXATION THERAPY ON CHANGES IN ANXIETY LEVEL IN PREGNANT WOMEN IN TM III IMPLEMENTING ANC - Nur Elly; Nabila Meiliarani; Sariman Pardosi; Dimas Dewa Darma (Poltekkes Kemenkes Bengkulu, 2023)
Anxiety is a psychological problem experienced by most pregnant women. The incidence of anxiety in the third trimester is increasing compared to the previous trimester. The research to prove the effect of guided imagery relaxation techniques on reducing the anxiety level of pregnant women. This type of research quasi-experimental design with pre and post test with control group design. The population was trimester III pregnant women with 40 samples (20 people in each group) obtained by using consecutive sampling. instruments research using the questionnaire Hamilton Rating for Anxiety (HRS- A). Analysis using Wilcoxon signed rank testand the Mann Whitney test. Results obtained the average anxiety score in the intervention group before the intervention was 22.60 after the intervention became 14.55. In the control group before the intervention19.80 and after the intervention 17.80.When compared between the two groups, the results of the Man-Whitney statistical test showed the 0.000. There is a significant difference decreased mean anxiety scores between groups. This proves is effect Guided imagery relaxation therapy is expected to be used as therapy to reduce anxiety trimester III pregnant women.